Sitios web como medio de comunicación interactiva del proceso de enseñanza-aprendizaje de la especialización informática en el primer bachillerato del colegio nacional mixto Atahualpa de Machala 2013-2014. - Cordero Cruz, Milton Antonio (2014)
The investigated subject met the standards established by the Technical University of Machala, going by applying each step of the investigation, for it has developed the conceptual framework has been under study, where the development of the conceptual framework has been contained who have direct relationship with the subject related websites as a means of interactive communication teaching-learning process, it has developed the hypothesis, the same that have been tested by applying the research instruments such as the survey of teachers and college students involved. The results of the research has focused on determining the incidence of websites in learning process in high school the first mixed national school Atahualpa city of Machala.